Silent Infection of Highly Pathogenic Avian Influenza Virus (H5N1) Clade 2.3.4.4b in a Commercial Chicken Broiler Flock in Italy - Federica Gobbo; Claudia Zanardello; Marco Bottinelli; Jane Budai; Francesca Bruno; Roberta De Nardi; Tommaso Patregnani; Salvatore Catania; Calogero Terregino (Viruses, 2022)
From October 2021 to January 2022, different incursions of clade 2.3.4.4b H5N1 HPAIV (Highly Pathogenic Avian Influenza Virus) occurred in several Italian regions with its main diffusion in Densely Poultry Populated Areas (DPPAs) of north-eastern Italy. Monitoring and control activities applied in the affected area clearly evidenced that turkeys and broilers were the most affected species, although several flocks of broilers at times resulted HPAIV H5N1 infected in absence of increased mortality and/or clinical signs. Thus, an approach based on sampling dead birds was adopted in the broiler sector to improve the early detection of infection; this protocol allowed us to confirm that 15 farms were HPAIV-infected with birds ready to be delivered to the slaughterhouse. The aim of this report is to describe the results of the diagnostic activities carried out in one HPAIV H5N1-infected broiler farm, three days after laboratory confirmation during the pre-movement testing without showing increased mortality or clinical signs. Thus, clinical signs, daily cumulative mortality rate (CMR), virus shedding, seroconversion, pathobiology of clade 2.3.4.4b H5N1 HPAIV as well as Avian Influenza Viruses (AIVs) environmental contamination were thoroughly examined in the infected holding. Such in-depth investigation demonstrated low infection prevalence in live birds, low environmental contamination, no seroconversion for AIVs, gross and microscopic findings compatible with systemic infection with peracute death in H5N1 HPAIV-infected birds.